The Urgency of Community Service Imposed as Punishment on Juvenile Delinquents: A Study of al- Shatibi’s Maqhasid al-Syariah Concept - Krismiyarsi, Krismiyarsi; Adityo, Rayno Dwi (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2025)
This study examines community service punishment in the context of law enforcement and the protection of children's rights and explores its objectives based on syariah or legal principles. This normative juridical research adopts statutory and conceptual approaches. Primary, secondary, and tertiary legal materials were used and processed descriptively and analytically. The research findings indicate that the imposition of community service punishment aligns with the objectives of criminal law under the theory of relative purposes, emphasising the rehabilitation of the behaviour of offenders. Juvenile delinquents are required to perform social activities for the community. In criminal law, community service punishment involves important aspects, including law enforcement's obligation to implement it and the recognition of children's rights. From the perspective of maqashid al-syariah by Al-Shatibi concept, this punishment aligns with the primary and urgent goals of Islamic law (ad-dharuriyat) by fulfilling three of the five essential elements that must be safeguarded according to syariah: the protection of religion (hifz ad-din), life (hifz an-nafs), and intellect (hifz al-aql). These elements suggest that enforcing community service as punishment is an urgent matter to enforce the law and protect children’s rights.